ANALISIS PERAN GURU DALAM PENGELOLAAN KELAS RENDAH DAN TINGGI DI SDN RAWU - Mutakarikah; A. Syachruroji; Firdaus (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The role of teachers in classroom management is one of the efforts to create a conducive learning atmosphere in the classroom. The efforts made by teachers in managing the class are due to the large number of students and the diversity of characters between individuals in one class, both in lower and upper elementary school classes, so that the role of teachers in managing the class is needed. This study aims to analyze the planning, process, supporting and inhibiting factors, and evaluation of the management of IA and VA classes at SDN Rawu. The study used a qualitative method with a descriptive approach. The results of the study showed that the planning of the management of IA and VA classes at SDN Rawu carried out by teachers was to design learning that was not monotonous and adjusted to the growth and development, abilities and characteristics of students in the class. In the process of managing IA and VA classes at SDN Rawu, teachers apply principles in managing the class to create a conducive learning atmosphere. The supporting and inhibiting factors in the management of IA and VA classes at SDN Rawu are the role of teachers as class managers and the number of students exceeding capacity. Classroom management carried out by teachers in the classroom shows that there is an evaluation, namely for an emotional deep approach and providing varied learning to prevent student boredom.